Genome-wide identification of acyl-CoA binding proteins and possible functional prediction in legumes - Ling, Juan; Li, Lingyu; Lin, Lifeng; Xie, Hui; Zheng, Yixiong; Wan, Xiaorong (Frontiers in Genetics, 2023)
Acyl-CoA-binding proteins (ACBPs), members of a vital housekeeping protein family, were detected in various animal and plant species. They are divided into four classes: small ACBPs (class I), ankyrin-repeat ACBPs (class II), large ACBPs (class III), and kelch-ACBPs (class IV). Plant ACBPs play a pivotal role in intracellular transport, protection, and pool formation of acyl-CoA esters, promoting plant development and stress response. Even though legume crops are important cultivated crops that provide vegetable oils and proteins for humans and serve as vegetables and green manure plants, legume ACBPs have received little attention. To comprehensively explore the functions of ACBPs in nine legumes (Lotus japonicus, Medicago truncatula, Glycine max, Vigna angularis, Vigna radiata, Phaseolus vulgaris, Arachis hypogaea, Arachis duranensis, and Arachis ipeanisis), we identified their family from genome-wide. We characterized the phylogenetics, gene structure, the conserved motif, chromosomal distribution and homology, subcellular localization, cis-elements, and interacting proteins. The results revealed that orthologs ACBPs of nine legumes had a high identity in gene structure and conserved motif. However, subcellular localization, cis-acting elements, and interaction protein analyses revealed potentially different functions from those previously reported, such as auxin-response cell cycle regulation, flavonoid biosynthetic genes regulation, gibberellin response, zein metabolism regulation, and ubiquitination. We believe that our findings will help researchers better understand the roles of ACBPs in legumes and encourage them to conduct additional research.